FILE DIN VIAŢA UNEI BISERICI Şl A UNUI MITROPOLIT (IV) - BOLDIŞOR, istoric, colaborator la Muzeul Literaturii Române „M. Kogâlniceanu", Veronica (BIBLIOPOLIS, 2020)
The author puts into circulation a set of documents - shown for the first time - that illustrates the state of incertainty, during the next 20 years of the Church and of the society before the Union of Bessarabia with Romania, at 27 march 1918. The author highlights the role of the Church, of the bishop Gurie Grosu in the establishment of a quiet life of Moldavians. Some documents show the unification of church life in Bessarabia and the Old Kingdom. Are capitalized the documents showing the existence of intrigue and misunderstanding within the Church, the attitude of personalities of Romanian culture etc.